To solve the linear-quadratic system given by the equations \( y = x^2 - 2x - 2 \) and \( y = 2x - 6 \) using the elimination method, we can start by setting the two expressions for \( y \) equal to each other:
\[ x^2 - 2x - 2 = 2x - 6 \]
Now, let's rearrange the equation to set everything to one side:
- Move \( 2x \) and \( -6 \) from the right to the left:
\[ x^2 - 2x - 2 - 2x + 6 = 0 \]
- Combine like terms:
\[ x^2 - 4x + 4 = 0 \]
- Factor the quadratic equation:
\[ (x - 2)^2 = 0 \]
- Solve for \( x \):
\[ x - 2 = 0 \implies x = 2 \]
Now that we have \( x = 2 \), we can substitute this value into one of the original equations to find \( y \). We can use the linear equation:
\[ y = 2x - 6 \]
Substituting \( x = 2 \):
\[ y = 2(2) - 6 \ y = 4 - 6 \ y = -2 \]
Thus, the solution to the system is:
\[ (x, y) = (2, -2) \]
To verify, we should check that this point also satisfies the quadratic equation \( y = x^2 - 2x - 2 \):
Substituting \( x = 2 \):
\[ y = 2^2 - 2(2) - 2 \ y = 4 - 4 - 2 \ y = -2 \]
Since both equations are satisfied, the solution to the system is:
\[ \boxed{(2, -2)} \]